Clinical medication review by a pharmacist of elderly people living in care homes: pharmacist interventions - Alldred, David P; Zermansky, Arnold G; Petty, Duncan R; Raynor, David K; Freemantle, Nick; Eastaugh, Joanne; Bowie, Peter (The International journal of pharmacy practice, 2007)
Objectives To describe the rate and nature of pharmacist interventions following clinical medication review of elderly people living in care homes. Setting Care home residents aged 65+ years, prescribed at least one repeat medication, living in nursing, residential and mixed care homes for older people in Leeds, UK. Method Analysis of data from care home residents receiving clinical medication review in the intervention arm of a randomised controlled trial. Intervention outcomes for each medicine were evaluated for each resident. Key findings Three‐hundred and thirty‐one residents were randomised to receive a clinical medication review and 315 (95%) were reviewed by the study pharmacist; 256 (77%) residents had at least one recommendation made to the general practitioner. For the 2280 medicines prescribed, there were 672 medicine‐related interventions: medicines for cardiovascular system (167 (25%)), nutrition and blood (121 (18%)), central nervous system (113 (17%)) and gastrointestinal conditions (86 (13%)) accounted for 487 (73%) of medicine‐related interventions. There were 75 non‐medicine‐related interventions. The most common interventions were ‘technical’ (225 (30%)), ‘test to monitor medicine’ (161 (22%)), ‘stop drug’ (100 (13%)), ‘test to monitor conditions' (75 (10%)), ‘start drug’ (76 (10%)), ‘alter dose’ (40 (5%)) and ‘switch drug’ (37 (5%)). Recommendations to stop a medicine were most common for CNS drugs (32 (32%)). The most common medicine to be recommended to be started was calcium and vitamin D (45 (59%)). Following a recommendation to test to monitor a medicine, 23 (14%) medicines required a change. Conclusions This study has demonstrated that clinical medication review by a pharmacist can identify medicine problems in approximately 80% of care home residents, requiring intervention in 1 in 4 of their prescribed medications.